2020
DOI: 10.1039/d0cy00639d
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and bimetallic metal catalysts based on Ni and Ru supported on alumina-coated monoliths for CO2 methanation

Abstract: A bimetallic catalyst consisting of Ni nanoparticles interspersed with atomic Ru on alumina coated monolith afforded higher activity than other mono and bimetallic catalysts in CO2 methanation, providing low pressure drop at high space velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…It was observed that the most suitable amount of ruthenium that improves the activity of the nickel catalyst is 1 wt%, the best value being 0.5 wt% in the case of platinum, reaching a high conversion at a lower temperature. A similar conclusion was found by Bustinza et al [26], by incorporating ruthenium in different proportions and order on a nickel (12.7 wt%) catalyst supported in alumina-coated monolith. In this case, the best conversion in the methanation reaction was achieved for catalysts with 1 wt% of Ru.…”
Section: Introductionsupporting
confidence: 86%
“…It was observed that the most suitable amount of ruthenium that improves the activity of the nickel catalyst is 1 wt%, the best value being 0.5 wt% in the case of platinum, reaching a high conversion at a lower temperature. A similar conclusion was found by Bustinza et al [26], by incorporating ruthenium in different proportions and order on a nickel (12.7 wt%) catalyst supported in alumina-coated monolith. In this case, the best conversion in the methanation reaction was achieved for catalysts with 1 wt% of Ru.…”
Section: Introductionsupporting
confidence: 86%
“…NiRu bimetallic catalysts are also viable candidates to be studied under more industrial-like conditions. Bustinza et al [ 99 ] prepared bimetallic NiRu structured monolithic catalysts with low Ru contents by homogeneously dispersing Ni and Ru precursors over alumina washcoated monoliths. Through an appropriate preparation method, Ni was supported in the form of small nanoparticles (2–4 nm), while Ru was atomically dispersed over the structured support.…”
Section: Promotion With Noble Metalsmentioning
confidence: 99%
“…Bustinza et al successfully designed bimetallic Ru-Ni based alumina coated monoliths using a consecutive impregnation method for CO 2 methanation with low pressure drop at high space velocities. 295 Recently, Chaudret and coworkers reported a surface engineering technique to fabricate an Fe-Ni catalytic network for selective magnetically induced CO 2 hydrogenation towards CH 4 under mild conditions (Fig. 18).…”
Section: Metal Nps As Active Sites For Co 2 Conversionmentioning
confidence: 99%